Straatsma Syndrome: A Case Report. - Novakovich, Marija (Optometry & Visual Performance, 2024)
Background: Myelination of the retinal nerve fiber layer can be found in approximately 1% of the population. It is a benign condition that appears as white and striated, with feathery borders around the peripapillary area. However, with additional findings of axial myopia and amblyopia, the triad can be classified as Straatsma syndrome. Case Report: A 10-year-old female presented with complaints of poor vision in the right eye. Upon examination, the right eye had an uncorrected visual acuity of 20/1000, while the left eye was 20/20. She failed all color test plates in the right eye, while the left eye had normal color vision. Refraction showed -10.50-1.00x045 (20/400- ) and plano. Dilated fundoscopy revealed dense myelination of the retinal nerve fiver layer superiorly, extending from the optic nerve head, as well as a lack of foveal light reflex in the right eye, while the left eye was unremarkable. Treatment for this patient included spectacle correction and close monitoring to assure that the condition was non-progressive. Conclusion: Straatsma syndrome is highlighted in this case report and features unilateral MRNF, high myopia, and amblyopia. Cases with high degrees of anisometropia typically have poor visual outcomes even with treatment. This indicates that there may be an organic etiology to Straatsma syndrome that is not yet understood.